COMORBIDITY OF EPILEPSY AND MENTAL DISORDERS - K. Naydenov; Y. Petkov; Iv. Manchev; V. Chengeliyska; D. Komsiyska (Trakia Journal of Sciences)
PURPOSE The purpose of this manuscript is to present the comorbidity between epilepsy and mental disorders. Epilepsy is a widespread, socially significant disease that has been the subject of medical literature and practice since ancient times. METHODS We have used a contingent of 100 epileptics, which were treated at the Neurological Clinic of the University of Medicine and Pharmacy "Prof. Dr. Stoyan Kirkovich" in Stara Zagora. RESULTS We found that in percentage ratio, out of the epileptic patients eighteen had mental illness. Out of these eighteen, depressive patients were 27.8%, which fell within the range indicated in the world literature. CONCLUSIONS As a conclusion, we suggest that the clinical assessment of the quality of life in epilepsy provides some opportunities for its improvement and should take its place in the bio-psychosocial approach to the disease.